Prospective Evaluation of Tumor Margin Status in Breast-Conserving Surgery: A Pathological and Surgical Perspective - Dwivedi, Mamta; Singh, Shruti; Tripathi, Anjani Kumar (Journal of Neonatal Surgery, 2025)
Aim: This study aims to evaluate tumor margin status in breast-conserving surgery (BCS) and assess its impact on the need for re-excision, axillary staging, and adjuvant therapy. Additionally, it explores molecular profiling to guide personalized treatment strategies. Materials and Methods: A prospective observational study was conducted on 120 female patients diagnosed with early-stage invasive breast carcinoma or ductal carcinoma in situ (DCIS). Wide local excision (WLE) was performed with intraoperative margin assessment. Sentinel lymph node biopsy (SLNB) and axillary lymph node dissection (ALND) were conducted as per nodal involvement. Histopathological analysis determined margin status, and immunohistochemistry (IHC) was used to assess hormone receptor expression, HER2 status, and Ki-67 index. Statistical analysis was performed using SPSS Version 25.0. Results: A majority of patients had negative margins, while a subset required re-excision due to close or positive margins. SLNB was performed in most cases, with a significant proportion showing nodal involvement. Molecular profiling identified a predominance of hormone receptor-positive tumors, with triple-negative breast cancer (TNBC) and HER2-positive subtypes influencing adjuvant therapy decisions. Postoperative management included radiation, hormonal therapy, chemotherapy, and targeted therapy as per molecular and pathological findings. Conclusion: This study underscores the importance of achieving clear margins in BCS to reduce re-excision rates and improve oncological outcomes. Lymph node status remains a critical prognostic factor, and molecular profiling plays a vital role in guiding systemic therapy. A multidisciplinary, personalized treatment approach integrating surgery, radiation, and systemic therapies is essential for optimizing long-term patient outcomes.